Continuous improvement of a face protection mask using quality function deployment - Montesinos González, Salvador; Vázquez Cid de León, Carlos; Ramírez Castillo, Eric Amín (Revista Venezolana de Gerencia, 2023)
This article aims to examine the applicability of the Quality Function Deployment (QFD) and the Kano model considering the expectations of the client, to a personal facial protection equipment against the Coronavirus 2019 (COVID-19), a disease that has caused a global pandemic, posing threats to public safety and social economies. In the first phase of the study, user requirements are identified at the local level based on current designs through the Kano model. This data is then merged with a Voice of Engineer (VoE) chart listing technical attributes and characteristics corresponding to items in Voice of Customer (VoC). The quality characteristics are then obtained by calculating the weights according to the level of importance, which are then transformed into measurable technical attributes in the House of Quality (HOQ). Through the weighting process using the pareto diagram, the main technical characteristics are identified, in which attention must be paid and the resources to be considered to satisfy said requirements must be evaluated. Finally, as a result, a 3D design is defined to make the prototype considering the needs of the client, which allows deducing the good applicability of the Kano-QFD model to carry out the development process of any product.